Serum metallome in pregnant women and the relationship with congenital malformations of the central nervous system: a case-control study - Jacopo Troisi; Luigi Giugliano; Laura Sarno; Annamaria Landolfi; Sean Richards; Steven Symes; Angelo Colucci; Giuseppe Maruotti; David Adair; Marco Guida; Pasquale Martinelli; Maurizio Guida (BMC, 2019)
Abstract Background Congenital malformations of the central nervous system (CNS) consist of a wide range of birth defects of multifactorial origin. Methods Concentrations of 44 metals were determined by Inductively Coupled Plasma Mass Spectrometry in serum of 111 mothers in the second trimester of pregnancy who carried a malformed fetus and compared them with serum concentrations of the same metals in 90 mothers with a normally developed fetus at the same week of pregnancy. Data are reported as means ± standard deviations. Results We found a direct relationship between congenital defects of the CNS and maternal serum concentration of aluminum: it was statistically higher in women carrying a fetus with this class of malformation, compared both to mothers carrying a fetus with another class of malformation (6.45 ± 15.15 μg/L Vs 1.44 ± 4.21 μg/L, p < 0.0006) and to Controls (i.e. mothers carrying a normally-developed fetus) (6.45 ± 15.15 μg/L Vs 0.11 ± 0.51 μg/L, p < 0.0006). Moreover, Aluminum abundances were below the limit of detection in the majority of control samples. Conclusion CAluminum may play a role in the onset of central nervous system malformations, although the exact Aluminum species and related specific type of malformation needs further elucidation.